Utilizing Reading Progress Feature In Microsoft Teams To Improve Speaking and Listening Competence Of English Foreign Language Learners - Rizky Eka Prasetya (Channing : Journal of English Language Education and Literature, 2022)
This study investigated whether the Reading Progress Feature substantially improves speaking abilities. This study used a quasi-experimental design using non-equivalent pretest-posttest control groups or comparison groups, and the population of this study comprised all undergraduate students of Universitas Prof Dr Moestopo Beragama. Purposive sampling was used to select 78 English Foreign Learners as the sample. The findings revealed a significant improvement in the EFL learners speaking comprehension after being evaluated using Reading Progress Feature to those who were not. There was also a significant mean difference in the EFL learners speaking comprehension after being evaluated using Reading Progress Feature than those not. On the other hand, technological Knowledge in Microsoft Team influences EFL learners speaking ability, and the evaluation from the Reading Progress Feature contributes to the speaking comprehension. Fluency contributed to speaking skills (aspects) to overall speaking accomplishment. As a result, it is possible to infer that employing Reading Progress Feature considerably improves EFL Learners' speaking abilities. The research's pedagogical conclusion is that instructors should consider Microsoft Team, including academic training in the English language online classroom since this might increase EFL learners' desire to speak and write by exposing them to real intriguing materials